Pharmacological Effects of Novel Peptide Drugs on Allergic Rhinitis at the Small Ribonucleic Acids Level - An, Li-Feng; Li, Zhan-Dong; Li, Lin; Li, Hao; Yu, Jian (Frontiers in Genetics, 2020)
Using an allergic rhinitis (AR) model, we evaluated the pharmacological effects of novel peptide drugs (P-ONE and P-TWO) at the small RNA (sRNA) level. Using high-throughput sequencing, we assessed the sRNA expression profile of the negative control, AR antagonist (positive control), P-ONE, and P-TWO groups. By functional clustering and Gene Ontology and KEGG pathway analyses, we found that sRNA target genes have a specific enrichment pattern and may contribute to the effects of the novel peptides. small RNA sequencing confirmed the biological foundations of novel and traditional AR treatments and suggested unique pharmacological effects. Our findings will facilitate evaluation of the pathogenesis of AR and of the pharmacological mechanisms of novel peptide drugs.